Design, development and fabrication of hydraulic drives screw press for metal forming operation / Mat Nawi Abd. Razak and Md. Said A. Rahman - Abd. Razak, Mat Nawi; A. Rahman, Md. Said (1987)
Metal Forming Processes are attaining increasing importance in production engineering. In the industry, mechanical and hydraulic presses play an important role. The increasing use of hydraulic drives and control has a significant influence an press operation. Hydraulic presses were known in the early development of machine design. With the development of hydraulic control system, the operation of mechanical presses were automated. The automation of machine tools is a factor of great important in the development of the engineering- industry which, in turn, forms the necessary basis for technical progress in the national economy. Automation increases the productivity of labour, reduces the physical strain on operators, improves the quality of products and ensures the reliable operation of equipment. Hydraulic drives are used in many fields of engineering but their main application in the area of machine tool operation.